Familial cardio‐facio‐cutaneous syndrome: Vertical transmission of the BRAF p.G464R pathogenic variant and review of the literature. Issue 2 (4th December 2020) - Rauen, Katherine A.; Maeda, Yoshiko; Egense, Alena; Tidyman, William E.
Abstract: Cardio‐facio‐cutaneous syndrome (CFC) is one of the RASopathies and is caused by germline mutations that activate the Ras/mitogen‐activated protein kinase (MAPK) pathway. CFC is due to heterozygous germline mutations in protein kinases BRAF, MEK1, or MEK2 and rarely in KRAS, a small GTPase. CFC is a multiple congenital anomaly disorder in which individuals may have craniofacial dysmorphia, heart issues, skin and hair anomalies, and delayed development. Pathogenic variants for CFC syndrome are usually considered de novo because vertical transmission has only been reported with MEK2 and KRAS. The index case was a 3‐year‐old male with features consistent with the clinical diagnosis of CFC. Sequencing revealed a previously reported heterozygous likely pathogenic variant BRAF p.G464R. Upon detailed family history, the index case's pregnant mother was noted to have similar features to her son. Targeted familial testing of the BRAF pathogenic variant was performed on the mother, confirming her diagnosis. Prenatal genetic testing for the fetus was declined, but postnatal molecular testing of the index case's sister was positive for the familial BRAF p.G464R variant. Functional analysis of the variant demonstrated increased kinase activity. We report the first identified vertically transmitted functional BRAF pathogenic variant. Our findings emphasize the importance of obtaining a comprehensive evaluation of family members and that activating pathogenic variants within the canonical MAPK cascade mediated by BRAF are compatible with human reproduction.